PENGARUH KETERAMPILAN TEKNIS, KETERAMPILAN SOSIAL, KETERAMPILAN KONSEPTUAL, DAN KETERAMPILAN MANAJERIAL TERHADAP KINERJA KEPALA SEKOLAH DASAR NEGERI DI WILAYAH JAKARTA PUSAT - SOPAN ADRIANTO (Universitas Negeri Jakarta, 2011)
The aim of this causal research is to obtain information related to the possibility that principals’ performance effected by technical skills, social skills, conceptual skills, and managerial skills.Survey was applied in this research which data have been analysed by path analysis after all variables put into a correlation matrix. In this research, the principals have been choosen as unit analysis and 114 samples selected randomly.The result of analysis find out that principals’ performance is effected directly by managerial skills, but effected indirectly by technical skills, social skills, and conceptual skills.Based on those findings it could be concluded that variation of principals’ performance might have been effected by the variation of technical skills, social skills, conceptual skills, and managerial skills.Therefore, technical skills, social skills, conceptual skills, and managerial skills should be put into the consideration in managing the principals’ performance of the State Elementary Schools in Central Jakarta.